1993
DOI: 10.1111/j.1745-3992.1993.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Coaching for the SAT: A Summary of the Summaries and an Update

Abstract: Why is it important to investigate the effectiveness of coaching for a test such as the SAT? How can you evaluate the effectiveness of coaching? What are some common misconceptions? What do we know and what is still unclear about the effects of coaching? What can we tell students and their families about the results of coaching studies ?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Indeed, 70 percent of privileged seniors use some test preparation activities (30 percent use more than one type of training), compared with less than half of low-SES students (Buchmann, Roscigno, and Condron 2006;see also Briggs 2001;McDonough 1994;NACAC 2009;Powers 1993). Affluent students also take the test multiple times, improving their scores (Vigdor and Clotfelter 2003).…”
Section: --American Sociological Reviewmentioning
confidence: 95%
“…Indeed, 70 percent of privileged seniors use some test preparation activities (30 percent use more than one type of training), compared with less than half of low-SES students (Buchmann, Roscigno, and Condron 2006;see also Briggs 2001;McDonough 1994;NACAC 2009;Powers 1993). Affluent students also take the test multiple times, improving their scores (Vigdor and Clotfelter 2003).…”
Section: --American Sociological Reviewmentioning
confidence: 95%
“…Numerous studies have explored the effects of test coaching and pretesting on performance in ability tests (e.g., Allalouf & BenShakhar, 1998;LeGagnoux, Michael, Hocevar, & Maxwell, 1990;Powers, 1985Powers, , 1987Powers & Rock, 1999). The major findings of these studies are summarized in the reviews by Bond (1989) and Powers (1993), and in various meta-analyses (Becker, 1990;DerSimonian & Laird, 1983;Kulik, Bangert-Drowns et al, 1984;Kulik, Kulik, & Bangert-Drowns, 1984;Messick & Jungeblut, 1981;Samson, 1985;Willson & Putnam, 1982). Table 1 documents the results of the most frequently cited meta-analyses by Becker (1990) and Kulik, Bangert-Drowns, and Kulik (1984).…”
Section: Effects Of Coaching and Pretestingmentioning
confidence: 94%
“…Previous empirical studies, particularly those in educational measurement, shed light on the effects of test preparation programs on cognitive test performance. For instance, Powers's (1993) summary of four previously published meta-analyses of preparation courses for the SAT ® and later studies showed that empirical results do not necessarily support a common belief that test preparation can lead to dramatic score improvement. According to Powers, the expected average score gains attributable to coaching were only 3 points on the SAT Verbal section and 17 points on the SAT Mathematics section (both on the scale of 200-800 points), suggesting that the effects of coaching on SAT scores may be modest at best.…”
Section: Effectiveness Of Test Preparation On Score Improvement and Tmentioning
confidence: 99%